2017
DOI: 10.1097/mpg.0000000000001434
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Status and Growth In 0–2‐Year‐Old Infants With Cow's Milk Protein Allergy

Abstract: The present study suggests that cow's milk protein allergy children have high prevalence of iodine deficiency and poor growth, however the 2 conditions were not associated. The subgroup of mainly breastfed infants was at higher risk of iodine deficiency compared to weaned infants. Subjects with feeding problems had increased risk of malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 34 publications
4
33
1
3
Order By: Relevance
“…Paediatric studies have attributed particular nutrients to specific excluded foods [e.g. calcium or iodine to cows’ milk]; however, as a result of the variety of food exclusion diets included in the present study and the wide distribution of some nutrients in a range of foods (e.g. selenium, niacin), it is not possible to attribute each micronutrient to the exclusion of a specific food.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Paediatric studies have attributed particular nutrients to specific excluded foods [e.g. calcium or iodine to cows’ milk]; however, as a result of the variety of food exclusion diets included in the present study and the wide distribution of some nutrients in a range of foods (e.g. selenium, niacin), it is not possible to attribute each micronutrient to the exclusion of a specific food.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of studies have investigated the diets of infants and children with milk and multiple food allergies, demonstrating differences in protein, calcium, zinc, vitamin D and iron intakes (5)(6)(7) . Additionally, research has shown that infants and children with cows' milk allergy (CMA) (8)(9)(10) or multiple food allergies (i.e. to a combination of to milk, egg, wheat, soya, fish tree nut and/or peanut) are at increased risk for impaired growth (5,6,(11)(12)(13)(14) , although overweight and obesity have also been reported (12) .…”
Section: Introductionmentioning
confidence: 99%
“…In Norway, the weaning diet of most children includes iodine-fortified baby foods, and children have a higher intake of dairy products than adults relative to their energy intake. Unless dairy products are excluded from the childÕs diet, Norwegian infants and toddlers most likely get adequate amounts of iodine (52). interaction terms between iodine from diet and iodine from supplements, and the models were adjusted for maternal age, BMI, parity, educational status, smoking during pregnancy, energy intake, fiber intake, folic acid supplement within the interval from 4 wk before to 8 wk after conception, total EPA/DHA intake, and random effects of sibling clusters.…”
Section: Figurementioning
confidence: 99%
“…3 Many authors have highlighted either insufficient dietary intake or actual deficiencies. 12,[110][111][112][113][114][115][116] If milk is excluded from the breastfeeding mothers' diet, nutrient intake in the maternal diet should be addressed as well. 12,[110][111][112][113][114][115][116] If milk is excluded from the breastfeeding mothers' diet, nutrient intake in the maternal diet should be addressed as well.…”
Section: Vitamin and Mineral Supplementationmentioning
confidence: 99%